210k views
4 votes
Solve the following system

Solve the following system-example-1
User Kuafu
by
5.0k points

1 Answer

4 votes

Solve for the first variable in one of the equations, then substitute the result into the other equation.

Point form:

(3,2), (3-2), (-3,2), (-3,-2)

Equation Form:

x = 3, y = 2.

x = 3, y = -2.

x = -3, y = 2.

x = -3, y = -2.

Hope this is helpful. <33

User Juan Rojas
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.